Application of Android-Based Mobile Learning Information System in Management of Learning Activities in Faculty of Science and Technology of Buddhi Dharma University - Paulus Yayan Christian; Wiyono Wiyono (Fakultas Sains dan Teknologi-Universitas Buddhi Dharma, 2020)
Teaching and learning activities, especially in Higher Education, from time to time develop along with the development of technology, especially information technology. Initially, the teaching and learning activities at the Faculty of Science and Technology of the Buddhist Dharma University (FST-UBD) used a manual system in the form of face-to-face class. The system (for several courses and meetings) developed into distance learning (e-learning) where lecturers and students did not meet in teaching and learning activities in the classroom but through the internet media. This distance learning system uses computer or laptop facilities. The e-learning system was developed into a mobile learning system, which is a distance learning system using an Android-based smartphone. In the mobile learning system, lecturers can provide lecture material and assignments to students. Students can view lecture material via cellphone and can download the material. Students can submit assignments to lecturers via cellphone. The University can provide information about the seminar to be held. Students can choose the seminar to be followed and can register for the seminar via cellphone. This application system can be run well and can help facilitate the process of teaching and learning activities for lecturers and students. Lecturers can upload material and assignments for students. Students can view / download material and submit assignments to the lecturer. The university can provide information about the seminar and the seminar registration process.